ANALISIS SENYAWA ATRAKTAN PADA PHYTOTELMATA YANG DIGUNAKAN SEBAGAI TEMPAT PERINDUKAN Aedes albopictus - fita wahidah; Ilmiah, Sitti Nur; Alif, Trisnani Alif (JURNAL TERAS KESEHATAN, 2023)
Dengue Hemorrhagic Fever (DHF) has still one of the problem diseases in Indonesia. There has increased in dengue cases in several parts of Indonesia since January 2020 and in the midst of the COVID-19. Very little information about natural breeding sites of Aedes especially of the phytotelmata such as Bambusa sp., Neoregelia spectabilis, Musa paradisiaca, and Cocos nucifera. Other than physical factors of plants, it is suspected that there are attractive compounds produced by these plants. The purpose of this study was to determine the chemical compounds that are attractants from plants used as breeding sites for Ae. albopictus. The research method was started by observation of the presence of Neoregelia spectabilis, Musa paradisiaca, Bambusa sp., and Cocos nucifera plants which contained Ae. albopictus on one of the plant body parts found. Then macerated, purified and analyzed for chemical content using GCMS. The results showed that there were differences in the chemical compounds of plants. The dominant chemical compound is tetracosane. Tetracosane is a chemical compound from the Alkane group. The alkana is an important role in plant interactions such as attractants in the oviposition of certain insects or as attractants for insect feeding activities.